The growth performance of pineapple (MD2) by using different planting material on mineral soil (Vegetetive stage) / Nurul Halwani Mohd Razally - Mohd Razally, Nurul Halwani (Faculty of Plantation and Agrotechnology, 2019)
This study was conducted to investigate the growth performance of pineapple by using different planting material on the mineral soil. At University Technology Mara (UiTM), Jasin Campus, Melaka. The objective for this study is to identify the growth performance of pineapple (MD2) by using different planting material on mineral soil. to determine the best planting material that used for growth performance of pineapple on mineral soil. The planting design for this experiment is Completely Randomize Design (CRD). There were have three treatments and also have three replications which are crown, slip and sucker. The parameter that have been collected is length of leaf, number of leaf, leaf area and plant height. We choose the MD2 as pineapple variety for study their growth performance on mineral soil. This study was conducted for 154 Days. The result shown the highest mean for length of leaf (37.05 cm), number of leaf (46.22 cm), width of leaf (4.44 cm) and the plant height (38.44 cm). Lastly, the determine which one of the best planting material can give the advantage for farmer so that they also can reduce the cost in maintenance for pineapple cultivation.